2016
DOI: 10.1016/j.plasmid.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Insect cell transformation vectors that support high level expression and promoter assessment in insect cell culture

Abstract: A somatic transformation vector, pDP9, was constructed that provides a simplified means of producing permanently transformed cultured insect cells that support high levels of protein expression of foreign genes. The pDP9 plasmid vector incorporates DNA sequences from the Junonia coenia densovirus that are involved in integration of the densovirus in insect cell chromosomes and a promoter/enhancer system that results in high levels of expression. The plasmid also contains two markers that permit selection of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Each of the three cloned Nasonia TRE sequences was linked with enhanced GFP (EGFP) as a visible reporter and then cloned into pDP9e (Shirk & Furlong, ) for functional assessment using somatic transformation. The pDP9e vector contains a hr5IE1DsRed fluorescent reporter cassette for establishment of transfection efficiency and comparison of expression levels.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each of the three cloned Nasonia TRE sequences was linked with enhanced GFP (EGFP) as a visible reporter and then cloned into pDP9e (Shirk & Furlong, ) for functional assessment using somatic transformation. The pDP9e vector contains a hr5IE1DsRed fluorescent reporter cassette for establishment of transfection efficiency and comparison of expression levels.…”
Section: Resultsmentioning
confidence: 99%
“…Once cloned into pGem‐T Easy, the EGFP fragment ( Bam HI‐ Ssp I fragment) from pEGFP‐N1 (TaKaRa, Mountain View, CA, USA) was cloned into the Bam HI‐ Zra I site 3′ of each of the three TRE sequences to produce pGem‐NVhsp70EGFP, pGem‐NVlsdpEGFP and pGem‐NVhsp90AEGFP. Each of these plasmids was restricted with Eco RI, filled with T4 DNA polymerase (NEB) according to the manufacturer's instructions, re‐restricted with Apa I and the NvTRE‐EGFP cassette was cloned into the ApaI‐BstZ17I site of pDP9e (Shirk & Furlong, ) to produce the somatic transformation vectors pDP9e‐NVhsp70EGFP, pDP9e‐NVlsdpEGFP and pDP9e‐NVhsp90AEGFP. Each of these plasmids was restricted with Kas I‐ Nde I to remove the NvTRE‐EGFP/hr5IE1DsRed cassettes, which were then cloned into the Kas I‐ Nde I of the LitpB1 piggyBac vector (Shirk & Furlong, ) to produce the germline transformation vectors LitpB‐NVhsp70EGFP/hr5IE1DsRed, LitpB‐NVlsdpEGFP/hr5IE1DsRed and LitpB‐NVhspEG90AEGFP/hr5IE1DsRed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main goal of our study was to develop a plasmid-based system for recovery of genetically modified DpCPV from cell cultures. Initially we tried to construct an insect cell line that stably expressed T7 polymerase, but due to the large size of the protein, we found that it could not be fully transcribed and expressed by several promoters (e.g., OpIE-1 [36], OpIE-2 [37], Drosophila metallothionein [38], Densoviral P9 [39]). Therefore, a helper virus like the recombinant vaccinia virus was adapted for expression of T7 polymerase.…”
Section: Discussionmentioning
confidence: 99%
“…The polyhedrin promoter is active during the late stage of baculoviral infection and has been used to express mammalian glycosyltransferases for the engineering of N -glycans in insect cells 10 . The actin promoter from B. mori is a constitutive promoter and has also been used for protein expression in insect cells 32, 33 . Only coexpression of P Pol -hGnT II and P Pol -hGalT I led to the expression of up to 35% biantennary terminally galactosylated N -glycans in silkworm pupae (Fig.…”
Section: Discussionmentioning
confidence: 99%